Determinants of Malaysian bank efficiency: evidence from bootstrap data envelopment analysis. (2015) - Sufian, Fadzlan
The paper follows Simar and Wilson's (2007) two-stage procedure to analyse the efficiency of the Malaysian banking sector. In the first stage, we employ the data envelopment analysis (DEA) method to compute the efficiency of individual banks during the period 1999 to 2008. We then use panel regressions to examine the impact of ownership on bank efficiency, while controlling for the potential impacts of contextual variables. The DEA results indicate an increase in efficiency over the sample period. The results from the panel regression suggest that productive efficiency is positively related to bank size, capitalisation, and foreign ownership. On the other hand, the publicly listed and government owned banks have been relatively inefficient in their intermediation function.